MANAGEMENT OF AND POTENTIAL RETURN ON PRIVATE INVESTMENTS IN LATVIAN SPORTS - Lauva, Mārtiņš; Grāvītis, Uldis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Latvian sports authorities under the Ministry of Education and Science are the main organisers of the sports life in Latvia. However, they have not been successful in providing equally good support to all athletes who need it. It is especially difficult to receive support for improving skills of individual athletes engaged in team sports. Often it is the individual mastery of an athlete that prohibits them from moving on to the adult level of sports of high achievement, even if the athlete was very talented and one of the best in the country, when he/she was young. The descriptive statistical method and content analysis were used to assess shortcomings in the allocation of finances in the Latvian sports industry. The study demonstrated that a successful process of private investments ensures a positive return on the investments, as well as the development of athletes. One way to build successful cooperation is by creating high-quality sports development centres or sports investment management companies, which will efficiently contribute to the athletes’ transition from youth to professional sports. The efficiency of the methodology developed can be demonstrated by creating a company, which would act as an example for attracting private investments in the development of athletes.